Measuring plot scale woodland structure using terrestrial laser scanning. Issue 4 (4th May 2018) - Muir, Jasmine; Phinn, Stuart; Eyre, Teresa; Scarth, Peter
Abstract: Terrestrial laser scanning (TLS) can be used to characterize a woodland site by measuring structural attributes of the vegetation community. In Australia, government funded programs monitor vegetation structure using manual field surveys to assess change and ecological condition. In this study, we examined whether structural attributes commonly assessed in woodland ecology surveys can be extracted from a single TLS scan. Attributes of the ground, shrub and overstory vegetation layers were evaluated at nine open woodland sites in central Western Queensland. We used 0.1 m voxels to aggregate returns. Our results show that, compared with field assessment by highly experienced ecologists, TLS can rapidly characterize structural attributes for tree canopy cover, maximum tree height, average tree height ( R 2  > 0.9) and average diameter at breast height ( R 2  = 0.77). However, we could not accurately determine shrub height, shrub canopy cover, shrub average height, ground cover (grass, litter and coarse woody debris) or the number of trees per hectare ( R 2  < 0.45). By analysing local minima in the histogram of the maximum height, we determined height thresholds for canopy strata, and applied these to determine the canopy layer with the most biomass – the ecologically dominant layer (EDL). While these results are promising for overstory assessment and defining canopy strata heights using TLS, they suggest that future research should focus on investigating improved classification methods to separate laser returns into shrub and tree objects for structural assessment at the plot scale. Abstract : In Australia, government funded programs monitor vegetation structure using manual field surveys to assess change and ecological condition. In this study, we examined whether structural attributes commonly assessed in woodland ecology surveys can be extracted from a single Terrestrial Laser Scanning (TLS) position, and used to assess vegetation condition. Although our results are promising for overstory assessment and defining canopy strata heights using TLS, they suggest that future research should focus on investigating improved classification methods to separate laser returns into shrub and tree objects for structural assessment at the plot scale.